Structural and rheological changes of texturized mung bean protein induced by feed moisture during extrusion - Hossain Brishti, Fatema; Chay, Shyan Yea; Muhammad, Kharidah; Mohammad Rashedi, Ismail Fitry; Zarei, Mohammad; Karthikeyan, Sivakumaran; Caballero Briones, F.; Saari, Nazamid (Elsevier BV, 2021)
Mung bean protein isolate was texturized at different feed moisture contents (30.0, 49.3, and 60.0%) at a constant temperature (144.57 °C) to evaluate the changes in protein profile, solubility, thermal, structural (at secondary and tertiary levels) and rheological properties. SDS-PAGE, surface hydrophobicity, circular dichroism, FTIR spectroscopy, and fluorescence analyses revealed protein unfolding, aggregation, and structural rearrangement as a function of feed moisture content. Extrusion at 49.3% feed moisture produced texturized mung bean protein (TMBP) with favourable partial denaturation, the formation of small aggregates, improved solubility, and digestibility with strong gel forming behaviour, whereas 30.0 and 60.0% moisture content resulted in complete protein denaturation, the undesirable formation of large aggregates and weak gels. In conclusion, protein denaturation and formation of aggregates can be controlled by manipulating feed moisture content during extrusion, with 49.3% feed moisture prompting favourable partial denaturation to produce TMBP with desirable qualities for use as a vegetarian-based meat extender.